Antioxidant asymmetry and acclimation temperature independently reflect fight outcome in male crickets. (September 2020) - Lorenz, Isabel; Fischer, Klaus; Beaulieu, Michaël
Abstract : Acclimation conditions may affect the fighting ability of individuals involved in agonistic contests through their oxidative status. For instance, exposure to high temperatures might increase the metabolic rate of opponents and their production of damaging reactive oxygen species (ROS). Animals investing more strongly in antioxidant defences to minimize the damaging action of heat-induced ROS may therefore be deprived of antioxidant defences and hence less able to sustain fight effort during subsequent contests. Here, we examined the interplay between acclimation temperature, oxidative status and fight outcome in male field crickets, Gryllus bimaculatus . Relative to nonfighting males, males involved in agonistic contests staged at 27 °C showed lower antioxidant defences when acclimated to cool conditions (19 °C) and higher oxidative damage when acclimated to higher temperatures (27 and 35 °C). This shows that fights represent an oxidative challenge, which is differently regulated depending on acclimation temperature. Furthermore, males with higher antioxidant capacity were more likely to win contests. Antioxidant defences therefore appear to contribute to the resource-holding potential of opponents, presumably because they reflect their ability to sustain the physical effort associated with fighting. Moreover, antioxidant defences may be used by opponents to assess their relative fighting ability to terminate contests before related costs become too high. However, antioxidant asymmetry reflected fight outcome only when both opponents were previously acclimated to the same thermal conditions. In contrast, when opponents were acclimated to different temperatures, males from the higher temperature were more likely to win these fights. This suggests that the effects of thermal conditions on fight outcome are independent of and preponderant over the effects of antioxidant defences. Antioxidant defences may still be an important determinant of fight outcome in the wild when opponents, occupying homogeneous habitats, are exposed to comparable conditions before fighting. Highlights: Oxidative status may mediate the effects of thermal conditions on fight outcome. In crickets, males with higher antioxidant defences were more likely to win fights. This advantage only occurred between opponents acclimated to the same temperature. Hence, antioxidant defences contribute to resource-holding potential of opponents. Yet, they do not mediate the effects of temperature on fight outcome.